How to live a low-carbon life : the individual's guide to tackling climate change - Goodall, Chris (Earthscan, 2010)
"Drastic reduction of carbon emissions is vital if we are to avoid a catastrophe that devastates large parts of the world. Governments and businesses have been slow to act - individuals need to take the lead now if we are to avoid climate chaos. Each Westener is responsible for an average 10 - 20 tonnes of carbon emissions each year (depending on where you live). In How to Live a Low-Carbon Life, Chris Goodall shows how easy it is to take responsibility, providing a comprehensive, one-stop reference guide to calculating your CO2 emissions and reducing them to a more sustainable 2 tonnes a year. This fully revised and expanded new edition takes into account new government targets on emissions reductions and includes up-to-date calculations and extensive graphics clearly laying out the path to a low-carbon life."--Publisher's description.